Determinants of household access to and participation in formal and informal credit markets in Malawi - Diagne, Aliou (International Food Policy Research Institute, 1999)
The paper uses the concept of credit limit to analyze the determinants of household access to and participation in informal and formal credit markets in Malawi. Households are found to be credit constrained, on average, both in the formal and informal sectors; they borrow, on average, less than half of any increase in their credit lines. Furthermore,they are not discouraged in their participation and borrowing decisions by further increases in the formal interest rate and/or the transaction costs associated with getting formal credit. This suggests that getting access to credit is much more important than its cost for these households. Hence, credit policies should focus on making access easier rather than providing credit with subsidized interest rates. The composition of household assets is found to be much more important as a determinant of household access to formal credit than the total value of household assets or landholding size. In particular, a higher share of land and livestock in the total value of household assets is negatively correlated with access to formal credit. However, land remains a significant determinant of access to informal credit. Therefore, poor households whose assets consist mostly of land and livestock but who want to diversify into nonfarm income generation activities may be constrained by lack of capital. As informal loans are usually too small to help poor households start a viable nonfarm business, these households may be forced to rely on farming as the sole source of income, despite its unreliability because of the frequency of drought in Malawi. Finally, formal and informal credit are found to be imperfect substitutes. In particular, formal credit, whenever available, reduces but does not completely eliminate informal borrowing. This suggests that the two forms of credit fulfill different functions in the household’s intertemporal transfer of resources.